Analysis of conducted emissions from an Electric Nacelle Anti-Ice power control system - Nothofer, A.; Tarisciotti, Luca; Zhou, Qian; Benson, Trevor M.; Greedy, Steve; Christopoulos, Christos (2016)
In this paper a high frequency model of the Electrical Nacelle Anti-Ice (ENAI) system is described for a typical aircraft application. The ENAI system, usually modelled only at the normal operating frequency, is modified in order to include a detailed high frequency description, which is of interest for conducted emission studies. Using this enhanced model it is possible to predict the conducted emissions resulting in a useful tool for Electromagnetic Interference (EMI) filter design. In this paper two different SCR switching modes are considered, Burst and Phase mode respectively. Experimental testing validates the proposed model, showing good agreement between predicted and measured conducted emissions.